Comparative Efficacy of Nano Zinc with Inorganic Zinc on Nutrient Digestibility and Mineral Availability in Barbari Goats - singh, Saurabh Pratap; Vaswani, Shalini; Kumar, Vinod; Anand, Mukul; Muneendra Kumar; Raju Kushwaha; Avinash Kumar (Indian Journal of Animal Nutrition, 2024)
The experiment was conducted to compare the effect of nano and inorganic Zinc supplementation on feed intake, nutrient utilization, growth performance and mineral availability in Barbari bucks. Twenty four Barbari bucks were randomly allocated into four groups having six bucks in each groups and fed for 90 days. Feeding regimen was similar in all the groups except that treatment groups were supplemented with 0.0 mg copper, 20.0 mg inorganic zinc, 20.0 and 10.0 mg of nano zinc per kg dry matter (DM; ppm) in four respective groups. Nutrients requirement of experimental bucks were met by feeding concentrate mixture, gram straw and corn silage as basal diet. Group fed on basal diet supplemented with 0.0 mg zinc/kg DM served as a control. Experimental bucks were monitored daily for DM intake (DMI) and fortnightly body weight change. At the end of the study, a digestion trial of 7 days was conducted to study the effect of inorganic and nano zinc supplementation on nutrients utilization. The present result revealed no significant (P>0.05) difference on growth performance, feed intake and nutrient digestibility in the experimental groups fed on either inorganic or nano form of supplemental Zn. No significant (P>0.05) effect on Ca, P, Cu and Fe intake, absorption and absorption (%) was observed on dietary supplementation of nano and inorganic Zn. However, the retention of Zn (mg/d) was significantly higher in NZn20 than NZn10 and IZn20 groups indicating better bioavailability of zinc when supplemented in nano form at 20 ppm level in Barbari bucks.